2022
DOI: 10.1126/scitranslmed.abm9151
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection drives an inflammatory response in human adipose tissue through infection of adipocytes and macrophages

Abstract: Obesity, characterized by chronic low-grade inflammation of the adipose tissue, is associated with adverse coronavirus disease 2019 (COVID-19) outcomes, yet the underlying mechanism is unknown. To explore whether severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection of adipose tissue contributes to pathogenesis, we evaluated COVID-19 autopsy cases and deeply profiled the response of adipose tissue to SARS-CoV-2 infection in vitro. In COVID-19 autopsy cases, we identified SARS-CoV-2 RNA in adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 133 publications
3
44
1
Order By: Relevance
“…The theory of viral reservoirs as an explanation for long-COVID symptoms has been put forward because viral antigens or intermediate molecules of viral replication have been detected in long-COVID cases despite negative PCR tests. 17,18,19,20 However, to our knowledge, this is the first evidence of a viral reservoir based on intrahost phylogenetics. These results call for further investigation to determine whether SARS-CoV-2 viral reservoir can be found in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 74%
“…The theory of viral reservoirs as an explanation for long-COVID symptoms has been put forward because viral antigens or intermediate molecules of viral replication have been detected in long-COVID cases despite negative PCR tests. 17,18,19,20 However, to our knowledge, this is the first evidence of a viral reservoir based on intrahost phylogenetics. These results call for further investigation to determine whether SARS-CoV-2 viral reservoir can be found in immunocompetent patients.…”
Section: Discussionmentioning
confidence: 74%
“…Mortality from severe pulmonary infection is highest among at-risk groups with chronic underlying conditions, including those with obesity and hypertension 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors found evidence that SARS-CoV-2 entry into macrophages might also not be dependent on ACE2 expression. Altogether, the new data by Martínez-Colón and colleagues suggest that adipose tissue could serve as an important target and reservoir for SARS-CoV-2 and that the related local inflammation and possible systemic inflammation might promote severe COVID-19 in people with obesity 3 .…”
mentioning
confidence: 99%
“…To understand the mechanisms involved in this relationship, Martínez-Colón and colleagues investigated the targets of SARS-CoV-2 within adipose tissue. Furthermore, they studied how infection might drive subclinical inflammation and functional alterations at the single-cell level 3 by analysing adipose tissue from patients with COVID-19 who had died. They detected SARS-CoV-2 RNA in several adipose depots and, by using RNA in situ hybridization, they also found SARS-CoV-2 in the cytoplasm of adipocytes and an adjacent mononuclear inflammatory infiltrate.…”
mentioning
confidence: 99%
See 1 more Smart Citation